PARAMETER DETERMINATION INMANUFACTURING PROGRESS CURVE WITH THREE POINTS OF DATA - Hennie Husniah; Asep K. Supriatna (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2004)
In this paper we discus a method to find the values of parameters in a manufacturing progress curve based on three pointsof data. In general to find better parameter estimation we need a lot of data. However, in some circumstances, the numbersof data are limited or even scarce, especially in the beginning of a manufacturing process. For this reason, we develop asimple method to determine the values of parameters if only three data are available. The curve we are dealing with is aninverse-like sigmoid that can describe a learning process in the beginning phase and has a lower bound in the long-termphase, hence a reasonably realistic curve.